2019
DOI: 10.3390/bs9050056
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver Reports of Screen Time Use of Children with Autism Spectrum Disorder: A Qualitative Study

Abstract: Screen based media have progressively become an integral part in the daily lives of children and youths with and without autism spectrum disorder (ASD). However, research that exclusively pursues the functionality of screen media use of children with ASD is extremely rare. Through a triangulated approach, the present study aims to fill this gap. We conducted 13 interviews with parents of children with ASD and supplemented this interview–study with an online survey including parents of children with ASD (n = 32… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 87 publications
0
9
0
1
Order By: Relevance
“…The current findings also have broader implications for the effective design of electronic screen media and screen-based learning activities for individuals with ASD. As is the case for children in general, electronic screen media is a preferred leisure activity for children with ASD (Montes, 2016; Shane & Albert, 2008; Stiller et al, 2019; Stiller & Mößle, 2018). Screen-based learning activities for individuals with ASD are also increasingly common in academic settings and intervention contexts (Shane & Albert, 2008; Stiller et al, 2019; Wainer & Ingersoll, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current findings also have broader implications for the effective design of electronic screen media and screen-based learning activities for individuals with ASD. As is the case for children in general, electronic screen media is a preferred leisure activity for children with ASD (Montes, 2016; Shane & Albert, 2008; Stiller et al, 2019; Stiller & Mößle, 2018). Screen-based learning activities for individuals with ASD are also increasingly common in academic settings and intervention contexts (Shane & Albert, 2008; Stiller et al, 2019; Wainer & Ingersoll, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…As is the case for children in general, electronic screen media is a preferred leisure activity for children with ASD (Montes, 2016; Shane & Albert, 2008; Stiller et al, 2019; Stiller & Mößle, 2018). Screen-based learning activities for individuals with ASD are also increasingly common in academic settings and intervention contexts (Shane & Albert, 2008; Stiller et al, 2019; Wainer & Ingersoll, 2011). However, numerous research groups have emphasized the importance of evaluating and refining electronic screen media as a learning tool for individuals with ASD (Gwynette et al, 2018; Odom et al, 2015; Shane & Albert, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Individuals diagnosed with autism spectrum disorders (ASD) commonly experience disturbances in their circadian rhythms, and commonly find difficulty in both falling asleep as well as sleeping through the night (Cohen et al, 2014; Devnani and Hegde, 2015; Mazurek and Sohl, 2016; Baker and Richdale, 2017; Shelton and Malow, 2021). Perhaps because of this difficulty sleeping at night, ASD patients spend more time exposed to the electronic screens at night compared with age-matched controls (Engelhardt et al, 2013; Stiller et al, 2019; Healy et al, 2020; Dong et al, 2021). It has been speculated that this exposure to DLaN via screens and other lighting sources could be detrimental to ASD populations.…”
Section: Introductionmentioning
confidence: 99%
“…Online social media platforms offer autistic individuals an alternative method of engaging in social interaction, and may be appealing due to the diminished levels of social demands (Lough et al, 2015) whilst at the same time drawing on strengths and interests in screen-based technology (Mazurek, 2013). Research has shown that groups with developmental disabilities spend greater amounts of time online compared to their typical counterparts (Kagohar et al, 2013;Mazurek & Wenstrup, 2013) and rely more on online communication for social interactions and relationships (Heasman & Gillespie, 2019;Stiller et al, 2019;Ward et al, 2018).…”
Section: Introductionmentioning
confidence: 99%